Optimizing Knowledge of Clean and Healthy Living Behavior among Santri in Az Zahro Islamic Boarding School through Public Health Podcast Media: Optimalisasi Pengetahuan Perilaku Hidup Bersih dan Sehat pada Santri di Pondok Pesantren Az Zahro, Curahdami Melalui Media Podcast Kesehatan Masyarakat Puskesmas Curahdami, Bondowoso - Gesit Wira Mustapa; Yudho Tri Handoko; Muhamad Zulfatul A'la; Hamidah Retno Wardani (KHD Production, 2024)
Clean and Healthy Behavior (PHBS) is a behavior carried out on consciousness as a result of learning that makes a person. Problems of clean and healthy living behavior are most commonly found in groups, for instance, in the Training Houses. This is often demonstrated by inappropriate environmental codes, including the availability of post-training health posts, the low level of knowledge of healthcare professionals such as managers and healthcare providers about clean and healthy living behaviour, and the high number of frequently occurring medical conditions such as scabies, diarrhea, and cold cough. This dedication to the community aims to provide knowledge and understanding of Clean and Healthy Living Behavior to the centurion so that there is a change in behavior and able to practice in his daily life in the Islamic boarding school Az Zahro Curahdami Bondowoso district. The method of implementation is done by means of giving education developed through viewing the public health podcast Primary Health Service Curahdami and is presented with questions and answers. Before conducting the education on Clean and Healthy Living Behavior, 75% of respondents had less knowledge, and 25% had sufficient knowledge about clean and healthy living behavior. Based on the results of observations showed that the activities of devotion to the community can improve the central knowledge about the behavior of a clean and healthy life through watching the Podcast Health Society Primary Health Service Curahdami district of Bondowoso.